Dual isolation of primary neurons and oligodendrocytes from guinea pig frontal cortex - Moloney, Roisin A.; Pavy, Carlton L.; Kahl, Richard G. S.; Palliser, Hannah K.; Hirst, Jon J.; Shaw, Julia C. (Frontiers in Cellular Neuroscience, 2024)
Primary cell culture is a technique that is widely used in neuroscience research to investigate mechanisms that underlie pathologies at a cellular level. Typically, mouse or rat tissue is used for this process; however, altricial rodent species have markedly different neurodevelopmental trajectories comparatively to humans. The use of guinea pig brain tissue presents a novel aspect to this routinely used cell culture method whilst also allowing for dual isolation of two major cell types from a physiologically relevant animal model for studying perinatal neurodevelopment. Primary neuronal and oligodendrocyte cell cultures were derived from fetal guinea pig's frontal cortex brain tissue collected at a gestational age of 62 days (GA62), which is a key time in the neuronal and oligodendrocyte development. The major advantage of this protocol is the ability to acquire both neuronal and oligodendrocyte cellular cultures from the frontal cortex of one fetal brain. Briefly, neuronal cells were grown in 12-well plates initially in a 24-h serum-rich medium to enhance neuronal survival before switching to a serum-free media formulation. Oligodendrocytes were first grown in cell culture flasks using a serum-rich medium that enabled the growth of oligodendrocyte progenitor cells (OPCs) on an astrocyte bed. Following confluency, the shake method of differential adhesion and separation was utilized via horizontally shaking the OPCs off the astrocyte bed overnight. Therefore, OPCs were plated in 12-well plates and were initially expanded in media supplemented with growth hormones, before switching to maturation media to progress the lineage to a mature phenotype. Reverse transcription-polymerase chain reaction (RT-PCR) was performed on both cell culture types to analyze key population markers, and the results were further validated using immunocytochemistry. Primary neurons displayed the mRNA expression of multiple neuronal markers, including those specific to GABAergic populations. These cells also positively stained for microtubule-associated protein 2 (MAP2; a dendritic marker specific to neurons) and NeuN (a marker of neuronal cell bodies). Primary oligodendrocytes expressed all investigated markers of the oligodendrocyte lineage, with a majority of the cells displaying an immature oligodendrocyte phenotype. This finding was further confirmed with positive oligodendrocyte transcription factor (OLIG2) staining, which serves as a marker for the overall oligodendrocyte population. This study demonstrates a novel method for isolating both neurons and oligodendrocytes from the guinea pig brain tissue. These isolated cells display key markers and gene expression that will allow for functional experiments to occur and may be particularly useful in studying neurodevelopmental conditions with perinatal origins.